ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS ADVERSE DRUG REACTION (ADR) REPORTING AMONGST THE COMMUNITY: A QUESTIONNAIRE BASED STUDY. - Dr. Vaishali Thakare; Dr. Mukta Jain; Ms. Vijetha Hegde; Ms. Sanaz Harsoliya; Mr. Aditya kankal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
ADR is defined as “a response to a drug that is noxious and unintended and occurs at dose normally used in a man for prophylaxis, diagnosis or therapy of disease or the modification of physiological function”.1